FUNCTIONAL STYLES OF ENGLISH AND UZBEK LANGUAGES - Nurullayeva Madina; Aziz Mukhamadiev (PEDAGOGS, 2024)
Annotation: The article analyzes the features of the functional styles of English and Uzbek languages, the complexity of understanding texts in different styles.